2019
DOI: 10.1063/1.5048297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pump wavelength on terahertz emission of a cavity-enhanced spintronic trilayer

Abstract: We systematically study the pump-wavelength dependence of terahertz pulse generation in thin-film spintronic THz emitters composed of a ferromagnetic Fe layer between adjacent nonmagnetic W and Pt layers. We find that the efficiency of THz generation is essentially flat for excitation by 150 fs pulses with center wavelengths ranging from 900 to 1500 nm, demonstrating that the spin current does not depend strongly on the pump photon energy. We show that the inclusion of dielectric overlayers of TiO 2 and SiO 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 25 publications
4
49
2
3
Order By: Relevance
“…Although our data in Fig. 1(b) seem to contradict recent results by Herapath et al, 24 where no wavelength dependence on THz generation was reported, we stress that the measurements in Ref. 24 were performed not only on a different material system, but, first of all, exclusively at infrared wavelengths (900-1500 nm).…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…Although our data in Fig. 1(b) seem to contradict recent results by Herapath et al, 24 where no wavelength dependence on THz generation was reported, we stress that the measurements in Ref. 24 were performed not only on a different material system, but, first of all, exclusively at infrared wavelengths (900-1500 nm).…”
contrasting
confidence: 88%
“…1(b) seem to contradict recent results by Herapath et al, 24 where no wavelength dependence on THz generation was reported, we stress that the measurements in Ref. 24 were performed not only on a different material system, but, first of all, exclusively at infrared wavelengths (900-1500 nm). High-energy, blue photons used in our studies are certainly more efficiently absorbed by metallic nanolayers and generate larger (up to a factor of three, according to our measurements) concentration of hot electrons that give rise to an enhanced spin current.…”
contrasting
confidence: 68%
“…[122] By shortening the pump-pulse width from 40 to 10 fs, a spectrum covering the full interval from 1 to 30 THz can be expected. [112] • STE operation is independent of the pump wavelength, [123,124] most likely because the primary function of the pump pulse is heating of the electron subsystem. Therefore, large-scale STEs can be driven by any high-power laser, independent of its output wavelength.…”
Section: Large-area Spintronic Thz Emittersmentioning
confidence: 99%
“…Numerous improvements can be anticipated, e.g., enhanced pump absorption, [124] optimization of F [125][126][127] and N materials, better heat dissipation by the substrate, shorter pump pulses, [112] and antenna structures. Numerous improvements can be anticipated, e.g., enhanced pump absorption, [124] optimization of F [125][126][127] and N materials, better heat dissipation by the substrate, shorter pump pulses, [112] and antenna structures.…”
Section: Large-area Spintronic Thz Emittersmentioning
confidence: 99%
“…When triggered by ultrafast femtosecond (fs) laser pulses, they generate pulsed terahertz (THz) electromagnetic radiation due to the inverse spin Hall effect (ISHE), a mechanism that converts the spin currents originating in the magnetized FM layer into transient transverse charge currents in the NM layer resulting in THz emission 2 . Different strategies have been followed in order to explore the THz amplitude and bandwidth of the signal: different material compositions of FM/NM systems with a variety of thicknesses 3–8 , ferri- and antiferromagnetic metal/Pt structures 9,10 , spintronic emitters assisted by metal-dielectric photonic crystal 11 , metallic trilayer structures with different interface materials 12–14 , THz emission from Rashba type interfaces 15,16 and THz emission using different excitation wavelengths 7,17 . The spin-to-charge-conversion mechanism was additionally probed in metallic and insulating magnetic/NM interfaces 1820 showing, however, much lower efficiency of the THz emission compared to the metallic magnetic layers.…”
Section: Introductionmentioning
confidence: 99%